2015
DOI: 10.1080/15384101.2015.1044175
|View full text |Cite
|
Sign up to set email alerts
|

p27Kip1participates in the regulation of endoreplication in differentiating chick retinal ganglion cells

Abstract: Nuclear DNA duplication in the absence of cell division (i.e. endoreplication) leads to somatic polyploidy in eukaryotic cells. In contrast to some invertebrate neurons, whose nuclei may contain up to 200,000-fold the normal haploid DNA amount (C), polyploid neurons in higher vertebrates show only 4C DNA content. To explore the mechanism that prevents extra rounds of DNA synthesis in these latter cells we focused on the chick retina, where a population of tetraploid retinal ganglion cells (RGCs) has been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…This cell death stimulation could be additionally enforced by the downexpression of CDKN2D and the overexpression of CDKN1B. [93,[126][127][128][129][130][131][132][133][134] ZINC FINGERS TRANSCRIPTION FACTORS…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…This cell death stimulation could be additionally enforced by the downexpression of CDKN2D and the overexpression of CDKN1B. [93,[126][127][128][129][130][131][132][133][134] ZINC FINGERS TRANSCRIPTION FACTORS…”
Section: Retinoic Acid Cycle (Rdh5 Mkv)mentioning
confidence: 99%
“…Modern genetic approaches investigating potential cell cycle re-entry in vertebrate brains began taking shape in the early 2000’s. In recent years, observations of bona fide polyploidy in neurons of the retinal ganglion of the chicken and mouse, cerebral cortex of the rat and neocortex of the mouse have been made using modern flow cytometry and high resolution imaging techniques ( Morillo et al, 2010 ; López-Sánchez and Frade, 2013 ; Ovejero-Benito and Frade, 2015 ; Martin et al, 2017 ; Jungas et al, 2020 ). Work from the Frade lab has shown that the neurons of the retinal ganglion become tetraploid in an E2F-dependent manner.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
“…The mechanism leading to neuronal tetraploidy depends on the activation of the neurotrophin receptor p75 ( 11 , 12 ), which induces the activation of p38 MAPK and the subsequent phosphorylation of E2F4 ( 14 ), a key regulator of the cell cycle. After DNA replication, Cdk1inactivation prevents differentiating 4C neurons from entering mitosis ( 15 ), while p27 Kip1 expression in these cells avoids further rounds of endoreplication ( 16 ). Somatic 4C neurons show extensive dendritic arbors and enlarged cell bodies ( 12 ), express the immediate early genes Erg-1 and c-Fos ( 11 ), known to respond to neuronal activity ( 17 , 18 ), and constitute specific neuronal populations that innervate defined target areas ( 12 ), thus indicating that 4C neurons are fully functional.…”
Section: Introductionmentioning
confidence: 99%